The ARP2/3 complex, acting cooperatively with Class I formins, modulates penetration resistance in Arabidopsis against powdery mildew invasion. Issue 9 (28th June 2021) - Qin, Li; Liu, Lijiang; Tu, Jiangying; Yang, Guogen; Wang, Sheng; Quilichini, Teagen D.; Gao, Peng; Wang, Hong; Peng, Gary; Blancaflor, Elison B.; Datla, Raju; Xiang, Daoquan; et al.
Abstract: The actin cytoskeleton regulates an array of diverse cellular activities that support the establishment of plant–microbe interactions and plays a critical role in the execution of plant immunity. However, molecular and cellular mechanisms regulating the assembly and rearrangement of actin filaments (AFs) at plant–pathogen interaction sites remain largely elusive. Here, using live-cell imaging, we show that one of the earliest cellular responses in Arabidopsis thaliana upon powdery mildew attack is the formation of patch-like AF structures beneath fungal invasion sites. The AFs constituting actin patches undergo rapid turnover, which is regulated by the actin-related protein (ARP)2/3 complex and its activator, the WAVE/SCAR regulatory complex (W/SRC). The focal accumulation of phosphatidylinositol-4, 5-bisphosphate at fungal penetration sites appears to be a crucial upstream modulator of the W/SRC–ARP2/3 pathway-mediated actin patch formation. Knockout of W/SRC–ARP2/3 pathway subunits partially compromised penetration resistance with impaired endocytic recycling of the defense-associated t-SNARE protein PEN1 and its deposition into apoplastic papillae. Simultaneously knocking out ARP3 and knocking down the Class I formin (AtFH1) abolished actin patch formation, severely impaired the deposition of cell wall appositions, and promoted powdery mildew entry into host cells. Our results demonstrate that the ARP2/3 complex and formins, two actin-nucleating systems, act cooperatively and contribute to Arabidopsis penetration resistance to fungal invasion. Abstract : ARP2/3 complex, acting cooperatively with Class I formins, modulates actin patch formation beneath fungal penetration sites, contributing to the penetration resistance of Arabidopsis against powdery mildew invasion.